Mycoplasma Diseases Of Ruminants - Nicholas, Robin (CABI, 2014)
Mycoplasmas, or more correctly mollicutes, the bacterial class which incorporates all the degenerate, wall-less bacteria, including mycoplasmas, acholeplasmas, ureaplasmas, spiroplasmas, entomoplasmas, mesoplasmas, phytoplasmas and the recently reclassified eperythrozoans and haemobartonellas, are characterized by their small genome size (0.58–1.38 Mbp), a low G+C content (23–40 mol%) of the genome and a permanent lack of a cell wall. Over 200 species have so far been described. According to the recent taxonomy of prokaryotes, the mollicutes belong to the phylum Firmicutes, which contains the Gram-positive bacteria and also comprises theBacilli andClostridia, from which the mollicutes have derived by a process of degenerative evolution. The terms mycoplasmas and molllicutes are used synonymously throughout this book.